Pengaruh Permainan Soccer Ball Bounce terhadap Keterampilan Passing Kaki Bagian dalam pada Pembelajaran Sepakbola - Kahan Tony Hendrawan; Novita Nur Synthiawati (MAN Insan Cendekia Jambi, 2026)
This study aimed to examine the effect of the Soccer Ball Bounce game on students' inside foot passing skills in football. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest-posttest design. The population consisted of all tenth-grade students at SMA PGRI Ploso, while the sample comprised 30 students from Class X-1 selected through cluster sampling. Data were collected using a psychomotor performance test. The results showed that the mean pretest score increased from 58.84 to 71.23 on the posttest. The paired t-test revealed a t value of 14.965, which exceeded the critical t value of 2.045 (df = 29, α = 0.05). These findings indicate that the implementation of the Soccer Ball Bounce game had a significant positive effect on students' inside foot passing skills among Class X-1 students at SMA PGRI Ploso.